2017
DOI: 10.1590/0001-3765201720160448
|View full text |Cite
|
Sign up to set email alerts
|

Grape juice increases the BDNF levels but not alter the S100B levels in hippocampus and frontal cortex from male Wistar Rats

Abstract: Several studies have shown that a high consumption of vegetables and fruits is consistently associated with a low risk of oxidative stress-induced diseases, which includes some degenerative diseases such as amyotrophic lateral sclerosis, Alzheimer and Parkinson. Therefore, the objective of this study is to verify the effects of conventional and organic grape juice in the modulation of the neurotrophic factor (BDNF) and astrocytic markers protein (S100B) in hippocampus and frontal cortex of Wistar rats. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…Flavonoids, a large part of polyphenols obtained from plants, are speculated to be effective in the treatment of several CNS disorders such as depression [34,35]. Altogether, these data support the idea previously suggested that natural products rich in flavonoids, which increase the BDNF levels, are promising [19].…”
Section: Sift Desksupporting
confidence: 84%
See 3 more Smart Citations
“…Flavonoids, a large part of polyphenols obtained from plants, are speculated to be effective in the treatment of several CNS disorders such as depression [34,35]. Altogether, these data support the idea previously suggested that natural products rich in flavonoids, which increase the BDNF levels, are promising [19].…”
Section: Sift Desksupporting
confidence: 84%
“…Interestingly, a significant BDNF enhancement after intervention was observed in GJG and GJEG women. These data could be partially related to experimental findings obtained by Dani and colleagues (2017) showing that 30 days of grape juice consumption was able to increase BDNF levels in frontal cortex and hippocampus from Wistar rats, suggesting that this period of consumption is enough to induce neuroplasticity [19]. In this study the authors showed that the flavonols content (mainly epicatechin) could provoke a significant increase in BDNF levels.…”
Section: Sift Desksupporting
confidence: 80%
See 2 more Smart Citations
“…The pathophysiology of depression is very complex, but the literature has shown the involvement of brain-derived neurotrophic factor (BDNF) as a crucial biomarker of this neural disorder. Some studies with phenolic compounds from blueberry and grape have shown that phenolic compounds are able to modulate important marker in brain tissue and could be an important factor to prevent brain diseases (Williams et al;Gomez-Pinilla and Nguyen, 2012;Dani et al, 2017). Therefore, further studies with guarana should investigate its role in modulation of BDNF.…”
mentioning
confidence: 99%